2013
DOI: 10.1590/s0080-623420130000600012
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedade e depressao entre homens e mulheres submetidos a intervencao coronaria percutanea

Abstract: RESUMOEstudo descritivo, transversal, correlacional, que objetivou verificar a associação entre a presença de ansiedade e depressão após a alta hospitalar em pacientes submetidos à intervenção coronária percutânea (ICP), segundo o sexo. Foram avaliados 59 pacientes submetidos à ICP e em acompanhamento ambulatorial nos primeiros sete meses após a alta hospitalar. Para avaliação de sintomas de ansiedade e de depressão foi utilizada a Escala Hospitalar de Ansiedade e Depressão (HADS). Para testar as possíveis ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…This study was conducted to increase our knowledge and fill the gap regarding the changes in anxiety levels among patients with CHD who have undergone first-time elective PCI at discharge time and at 6 months later. All characteristics of participants in this study were comparable with the characteristics of participants in previous studies, 18,29,30 except that there were more men in our study than in some previous studies. 29,30 Having more male than female subjects could be attributed to the high prevalence of CHD among Jordanian men as a result of having a significantly higher prevalence of CHD risk factors such as smoking, diabetes, hypertension, low levels of high-density lipoprotein cholesterol, and hypercholesterolemia than women.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study was conducted to increase our knowledge and fill the gap regarding the changes in anxiety levels among patients with CHD who have undergone first-time elective PCI at discharge time and at 6 months later. All characteristics of participants in this study were comparable with the characteristics of participants in previous studies, 18,29,30 except that there were more men in our study than in some previous studies. 29,30 Having more male than female subjects could be attributed to the high prevalence of CHD among Jordanian men as a result of having a significantly higher prevalence of CHD risk factors such as smoking, diabetes, hypertension, low levels of high-density lipoprotein cholesterol, and hypercholesterolemia than women.…”
Section: Discussionsupporting
confidence: 87%
“…Evidence further suggests that there is no consensus with regard to the level of anxiety based on patients' demographic variables. For example, Furuya et al 18 showed that men have more frequent anxiety than women after PCI (66.7% vs 56.3%). A contradictory study showed that among patients undergoing PCI, women reported a significantly higher anxiety level compared with men (50.4 ± 26.5 vs 41.5 ± 26.8) 19 .…”
mentioning
confidence: 99%
“…Otro estudio mostró poca asociación entre la ansiedad estando en el pre-operatorio de cirugía cardíaca con la edad (r=0,226; p<0,001), mayores valores entre las mujeres, correlación negativa con escolaridad (p<0,001) y escores mayores entre pacientes con compañeros que entre los sin (solteros, viudos y divorciados) (18) . El género femenino fue asociado de forma estadísticamente significativa a mayores escores de depresión en un estudio realizado con pacientes con enfermedad cardíaca postintervención percutánea (19) .…”
Section: Discussionunclassified
“…Therefore, although PCI can provide temporary relief of patients' symptoms, patients' anxiety and depression do not improve after PCI, and their quality of life remains poor due to the continued persistence of risk factors for coronary heart disease, the consequences of the procedure and the continued need for long-term medication afterward. 12,13 With the increase in people's standard of living, there is an ever-growing demand for quality of life and an increasing focus on the enjoyment of life. Quality of life is now used as an essential indicator to evaluate health.…”
Section: Statement Of Principal Findingsmentioning
confidence: 99%
“…10,11 Due to the pain associated with the disease, the risk of recurrence, the need for long-term standardized medication and a good lifestyle, and the sudden lack of medical care after discharge, post-PCI patients generally face greater stress after discharge, with anxiety, depression, and low quality of life. 12,13 Poor lifestyle, stress, anxiety, and depression are risk factors for the recurrence of coronary heart disease. 14,15 To mitigate the anxiety and depression of postoperative patients with PCI after discharge and to improve their quality of life, we used WeChat to carry out remote health management.…”
Section: Introductionmentioning
confidence: 99%